Public Attention and Policy Responses to Covid-19 Pandemic - Cevat Giray Aksoy; Michael Ganslmeier; Panu Poutvaara (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Early non-pharmaceutical interventions (NPI) significantly reduced the death toll of the Covid-19 pandemic. Yet, there are vast differences in how quickly governments implemented NPIs. In this paper, we analyze the role of public attention, measured as the share of daily Google searches in a country related to Covid-19, in the timing of the NPI responses. We first show that public attention depends strongly on whether there are cases in own country. We then show that countries with high levels of public attention are more likely to implement non-pharmaceutical interventions, even after controlling for the number of cases and deaths. Finally, we show that the extent to which a government responds to public attention is highly dependent on the country's institutional quality. The positive effect of public attention on policy implementation is driven entirely by countries with good institutions.
Keywords: D72; D78; D83; H12; I18; 330; Covid-19; non-pharmaceutical interventions; public attention; institutional quality